Síndrome da deleção do braço curto do cromossomo 18: avaliação clínica e citogenômica - Meloni, Vera de Freitas Ayres [UNIFESP] (2016)
Chromosome 18p deletion syndrome [del(18p)] (OMIM 146390) has been well described in the literature with over 300 patients reported on, but few of them evaluated by cytogenomic techniques. Objective: We studied 12 patients with 18p deletion based on clinical, developmental and cytogenomic findings. Methods: The patients were evaluated by a specific clinical protocol, including immunological, endocrinological and neuropsychological assessments. The cytogenetic study was performed by G-banding karyotype, SNP-array (Genome-Wide Human SNP Array 6.0, Affymetrix) and FISH-BAC techniques. Results: A total of 12 patients, seven males and five females, previously diagnosed with 18p deletion were evaluated. The patients were classified in three groups according to the cytogenomic findings, as follows: five with pure 18p deletion (group I), two with ring chromosome 18 (group II) and five with 18p deletion associated with duplication or deletion of another chromosome (group III). Conclusions: The results showed a wide variation in intra- and inter-chromosomal rearrangements in patients, both inherited as de novo, as well as a wide variability of phenotypic manifestations and comorbidities. Although the literature indicates 18p11.1 as the most frequent breakpoint, our patients presented different breakpoints: 18p11.21 (5/12), 18p11.23 (2/12), 18p11.31 (4/12), and 18p11.32 (1/12). The main clinical findings were: proportionate short stature; microcephaly; ectopic pituitary; growth hormone deficiency; hypothyroidism; intellectual disability; cardiac anomalies; scoliosis; and keratosis pilaris. The distinguished facial dysmorphic features were: ocular hypertelorism; ptosis; and strabismus.The neuropsychological assessments showed IQ scores from borderline intellectual functioning to moderate intellectual disability. The SNP-array technique permitted a better chromosome breakpoint definition and, associated to the specific clinical protocol, provided a better genotype-phenotype correlation revealing genes that might influence the patient?s phenotype. Some genes located in the 18p deleted segment seem to play important roles in the patient?s phenotype, such as TGIF1, GNAL, LAMA1 and LPIN2 genes. The clinical protocol associated with cytogenomic results provided the recognition of relevant genes to the clinical manifestations found, such as holoprosencephaly microforms, keratosis pilaris, cryptorchidism, scoliosis and IgA deficiency. In addition, the multidisciplinary approach of this study allowed making recommendations for medical and neuropsychological evaluation on 18p deletion patients for better clinical monitoring and appropriate genetic counseling for each family.